Development of a Proximity Labeling System to Map the Chlamydia trachomatis Inclusion Membrane - Rucks, Elizabeth A.; Olson, Macy G.; Jorgenson, Lisa M.; Srinivasan, Rekha R.; Ouellette, Scot P. (Frontiers in Cellular and Infection Microbiology, 2017)
Chlamydia grows within a membrane-bound vacuole termed an inclusion. The cellular processes that support the biogenesis and integrity of this pathogen-specified parasitic organelle are not understood. Chlamydia secretes integral membrane proteins called Incs that insert into the chlamydial inclusion membrane (IM). Incs contain at least two hydrophobic transmembrane domains flanked by termini, which vary in size and are exposed to the host cytosol. In addition, Incs are temporally expressed during the chlamydial developmental cycle. Data examining Inc function are limited because of (i) the difficulty in working with hydrophobic proteins and (ii) the inherent fragility of the IM. We hypothesize that Incs function collaboratively to maintain the integrity of the chlamydial inclusion with small Incs organizing the IM and larger Incs interfacing with host cell machinery. To study this hypothesis, we have adapted a proximity-labeling strategy using APEX2, a mutant soybean ascorbate peroxidase that biotinylates interacting and proximal proteins within minutes in the presence of H2O2 and its exogenous substrate, biotin-phenol. We successfully expressed, from an inducible background, APEX2 alone, or fusion proteins of IncATM (TM=transmembrane domain only), IncA, and IncF with APEX2 in Chlamydia trachomatis serovar L2. IncF-APEX2, IncATM-APEX2, and IncA-APEX2 localized to the IM whereas APEX2, lacking a secretion signal, remained associated with the bacteria. We determined the impact of overexpression on inclusion diameter, plasmid stability, and Golgi-derived sphingomyelin acquisition. While there was an overall impact of inducing construct expression, IncF-APEX2 overexpression most negatively impacted these measurements. Importantly, Inc-APEX2 expression in the presence of biotin-phenol resulted in biotinylation of the IM. These data suggest that Inc expression is regulated to control optimal IM biogenesis. We subsequently defined lysis conditions that solubilized known Incs and were compatible with pulldown conditions. Importantly, we have created powerful tools to allow direct examination of the dynamic composition of the IM, which will provide novel insights into key interactions that promote chlamydial growth and development within the inclusion.